PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDNEGERI 008 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Naser, Muhammad; ', Lazim N; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by lowmathematics learning outcomes ofstudents, with a grade average of 58.43. While the completeness criteria Minimumvalue (KKM) Mathematics is 65 Among students numbering 35 people only 12students who achieve KKM with classical completeness 34.28%. This research isClassroom Action Research (CAR) conducted aims to improve learning outcomesMathematics Elementary School fifth grade students Segajah 008 River byapplying learning model of Problem Solving. Data collection instruments in thisthesis is the sheet activities of teachers and students and learning outcomes. Thisthesis presents the results obtained by studying the average learning outcomemeasures 58.43 before rising 26.88% to 74.14 in cycle I. In the second cycleincreased by 34.70% to an average of 78.71. activities of teachers in the firstcycle the first meeting of the percentage obtained with the category of less than55%, the second meeting had to be 70%. Furthermore, the first meeting of thesecond cycle activity scores of teachers 75% increase with both categories, at thesecond meeting increased to 90% with very good category. The results of the dataanalysis of student activity in the first cycle to 55% with less category, at thesecond meeting 65% In this cycle of learning activities of students alreadyunderstand the application of learning models Problem Solving. And the secondcycle activity score 85% increase of students with very good category. At thesecond meeting increased to 90% with very good category. The results of thestudy at 008 River Elementary School fifth grade Segajah prove that theapplication of problem solving learning model to improve learning outcomesMath 008 fifth grade students of SDN Segajah River.Keywords: Problem Solving, Mathematics Learning Outcomes